2017
DOI: 10.3847/1538-4357/aa7b82
|View full text |Cite
|
Sign up to set email alerts
|

Fast Magnetic Reconnection: “Ideal” Tearing and the Hall Effect

Abstract: One of the main questions in magnetic reconnection is the origin of triggering behavior with on/off properties that accounts, once it is activated, for the fast magnetic energy conversion to kinetic and thermal energies at the heart of explosive events in astrophysical and laboratory plasmas. Over the past decade progress has been made on the initiation of fast reconnection via the plasmoid instability and what has been called "ideal" tearing, which sets in once current sheets thin to a critical inverse aspect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 37 publications
(35 reference statements)
6
57
0
Order By: Relevance
“…The evolution is similar with Run 0 at t ≤ 5: a secondary current sheet is formed and stretched along x direction with thickness a 1 ≈ 0.0016. Then the secondary current sheet breaks into small plasmoids at t ≈ 5, earlier than Run 0 as expected: tearing instability has larger growth rate with Hall term [20]. Very soon after the break up of the secondary current sheet, a single X-point configuration, which is a typical structure of Hall-reconnection, is formed (between t = 5.2 and t = 5.6).…”
Section: Time Evolution and The Structure Of The Current Sheetsupporting
confidence: 55%
“…The evolution is similar with Run 0 at t ≤ 5: a secondary current sheet is formed and stretched along x direction with thickness a 1 ≈ 0.0016. Then the secondary current sheet breaks into small plasmoids at t ≈ 5, earlier than Run 0 as expected: tearing instability has larger growth rate with Hall term [20]. Very soon after the break up of the secondary current sheet, a single X-point configuration, which is a typical structure of Hall-reconnection, is formed (between t = 5.2 and t = 5.6).…”
Section: Time Evolution and The Structure Of The Current Sheetsupporting
confidence: 55%
“…At each step, the Lundquist number decreases, and finally they will cross the critical S at which further disruption is quenched. However, at those scales where S becomes small enough, kinetic effects, explored in (Pucci et al 2017), become fundamental. We plan to address this question in subsequent works.…”
Section: Resultsmentioning
confidence: 99%
“…with d i0 being the asymptotic value of the ion inertial length. The Hall term is not negligible when the ion inertial length becomes comparable to the width δ of the inner resistive layer of the tearing instability [14]. For the fastest growing mode, the inner width δ is described by the equation δ/a S −3/10 a ∆ 1/5 [15], where S a is given in Eq.…”
Section: Including the Hall Term In The Ideal Tearing Instabilitymentioning
confidence: 99%
“…We can identify three regimes: a MHD regime (η H S −1/2 ) where the Hall term does not play a relevant role, a mild Hall regime (η H S −1/2 ), where the ion inertial scale is comparable to the thickness of the inner layer, and a strong Hall regime (η H S −1/2 ), where reconnection is dominated by the Hall effect and the classic theory of the tearing instability is no longer valid. The linear phase of the tearing instability in these three regimes has already been investigated by [14] in the case of a Harris current sheet in pressure equilibrium. They verified the existence of these regimes, and showed that the linear growth rate start increasing for, e.g., values d i /δ ∼ 3 at S = 10 6 .…”
Section: Including the Hall Term In The Ideal Tearing Instabilitymentioning
confidence: 99%